Case Report: Unmanipulated Matched Sibling Donor Hematopoietic Cell Transplantation In TBX1 Congenital Athymia: A Lifesaving Therapeutic Approach When Facing a Systemic Viral Infection - Chitty-Lopez, Maria; Duff, Carla; Vaughn, Gretchen; Trotter, Jessica; Monforte, Hector; Lindsay, David; Haddad, Elie; Keller, Michael D.; Oshrine, Benjamin R.; Leiding, Jennifer W. (Frontiers in Immunology, 2022)
Congenital athymia can present with severe T cell lymphopenia (TCL) in the newborn period, which can be detected by decreased T cell receptor excision circles (TRECs) on newborn screening (NBS). The most common thymic stromal defect causing selective TCL is 22q11.2 deletion syndrome (22q11.2DS). T-box transcription factor 1 (TBX1), present on chromosome 22, is responsible for thymic epithelial development. Single variants in TBX1 causing haploinsufficiency cause a clinical syndrome that mimics 22q11.2DS. Definitive therapy for congenital athymia is allogeneic thymic transplantation. However, universal availability of such therapy is limited. We present a patient with early diagnosis of congenital athymia due to TBX1 haploinsufficiency. While evaluating for thymic transplantation, she developed Omenn Syndrome (OS) and life-threatening adenoviremia. Despite treatment with anti-virals and cytotoxic T lymphocytes (CTLs), life threatening adenoviremia persisted. Given the imminent need for rapid establishment of T cell immunity and viral clearance, the patient underwent an unmanipulated matched sibling donor (MSD) hematopoietic cell transplant (HCT), ultimately achieving post-thymic donor-derived engraftment, viral clearance, and immune reconstitution. This case illustrates that because of the slower immune recovery that occurs following thymus transplantation and the restricted availability of thymus transplantation globally, clinicians may consider CTL therapy and HCT to treat congenital athymia patients with severe infections.